PENDAMPINGAN PBM DENGAN PENDEKATAN REACT BERBASIS SADAR LINGKUNGAN PASCA ERA NEW NORMAL - Algiranto Algiranto; Rikardus Feribertus Nikat (LP4MK STKIP PGRI Lubuklinggau, 2023)
The profile of the service partner is the teacher of SMP Muhammadiyah Kartosentanan, Merauke, which is located on Jalan Mopah. SMP Muhammadiyah Kartosentono Merauke is one of the pilot schools that provides secondary level education and teaching. One of the problems experienced today is that almost all educational institutions are ready to carry out the learning process after the new normal era. The learning in question is a learning tool, an assessment system and a learning delivery method. Based on studies related to problems with partners, first, most teachers find it difficult to be ready for normal learning because of the pandemic which requires the online teaching and learning process to follow social distancing rules in learning. Second, students are still traumatized by the pandemic situation that forces every activity at school to be carried out online. The REACT approach by Michael Crawford is Relating, Experiencing, appliying, Cooperating and Transfering. Middle School teachers of Muhammadiyah Kartosentanan are expected partners from this service activity, namely the delivery of skills in the learning process with the REACT approach to support the post-new normal era of teachers in the learning system. The ultimate goal is that the teacher is able to master all learning activities in the post new normal era. In addition, this service is a form of reflection for academics at universities or writers' institutions in developing efficient, effective and creative learning systems.